Equity valuation : Group EDP : 2011 - Morgado, Gonçalo Filipe Vasco (2014)
Valuation is as important as difficult and is far from being an exact science. The aim of this dissertation is to analyze EDP – Energias de Portugal, SA under the theories and works of many authors that give all their work to develop the best techniques and assumptions to came up with the best valuation possible. Still, the debate will continue and many other opinions will appear. Group EDP is enormous. Hence, this dissertation focuses on the most important business segment: Electrical business in Portugal and Spain. This work is done meanwhile Portugal is under financial intervention and it will affect directly EDP as it will be totally private. The final objective is to compare my work with Caixa Banco de Investimento in their report of December 2010.